2017
DOI: 10.1111/ivb.12194
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity of the invasive marine gastropodCrepidula fornicatanear the current northern extreme of its range

Abstract: The calyptraeid gastropod Crepidula fornicata is native to the eastern coast of the United States but has now become an extremely successful invader along much of the European coastline. As the northern limit of its spread is thought to be determined by an inability of adults to tolerate prolonged exposure to low winter temperatures, this study sought to compare the fecundity of females collected from two sites along the Norwegian coastline with that of females collected from Rhode Island, USA. Few other studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…The Atlantic slippersnail, Crepidula fornicata, exemplifies a marine intertidal and estuarine invertebrate whose adults exhibit remarkable resilience to most predicted environmental conditions of climate change (Ries et al, 2009;Diederich and Pechenik, 2013;Noisette et al, 2016), yet whose early life stages appear somewhat more vulnerable (Noisette et al, 2014;Bashevkin and Pechenik, 2015;Maboloc and Chan, 2017). Indeed, fecundity can be higher for intertidal individuals than for neighboring subtidal individuals (Pechenik et al, 2017b) and higher fecundities have also been observed at the northern range extreme when compared to their range center (Pechenik et al, 2017a). Adult C. fornicata have even demonstrated increased calcification under intermediate pCO 2 conditions (605 and 903 ppm; Ries et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The Atlantic slippersnail, Crepidula fornicata, exemplifies a marine intertidal and estuarine invertebrate whose adults exhibit remarkable resilience to most predicted environmental conditions of climate change (Ries et al, 2009;Diederich and Pechenik, 2013;Noisette et al, 2016), yet whose early life stages appear somewhat more vulnerable (Noisette et al, 2014;Bashevkin and Pechenik, 2015;Maboloc and Chan, 2017). Indeed, fecundity can be higher for intertidal individuals than for neighboring subtidal individuals (Pechenik et al, 2017b) and higher fecundities have also been observed at the northern range extreme when compared to their range center (Pechenik et al, 2017a). Adult C. fornicata have even demonstrated increased calcification under intermediate pCO 2 conditions (605 and 903 ppm; Ries et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The complete weight of the snail also correlates with its fecundity, as the number of eggs will also have an effect on its total body weight. The positive correlation between fecundity and body size also occurs in other gastropod members such as Conus pennaceus (Perron 1983); Limpet species Notoacmea petterdi, Patelloida alticostata, and P. latistrigata (Creese 1980); Invasive gastropod Crepidula fornicata (Pechenik et al 2017).…”
Section: Fecunditymentioning
confidence: 86%
“…In parts of northern Europe, it reaches high density in both intertidal and subtidal areas (Blanchard, 1997 ; Thieltges et al ., 2004 ; Bohn et al ., 2012 ). The success of non-native populations of slipper limpets has been attributed to several factors including high fecundity, where females can produce several batches of eggs annually and their brooding ability of fertilized eggs that reduces larval mortality (Pechenik et al ., 2017 ) together with an extended reproductive period (e.g. Ricard et al ., 2006 ; Bohn et al ., 2012 ).…”
Section: Discussionmentioning
confidence: 99%